Avaliação do aporte e distribuição da matéria orgânica em sedimentos superficiais do estuário do Rio São Francisco usando biomarcadores lipídicos - Santos, Lukas Gomes Gadelha Vieira (2019)
São Francisco River has been widely affected due to the presence of several anthropogenic activities such as the reduction of water flux by dams and reservoirs along the basin, incorrect discharge of wastewater, agriculture and boating activities for economic and subsistence purposes. These activities have been introducing several pollutants in the São Francisco River Estuary, which might represent a risk not only for the biota but also for the inhabitants who live in the area. Thereby, this study aimed to evaluate the origin and distribution of the sedimentary organic matter in the São Francisco River Estuary using lipid biomarkers. Twenty two sediment samples were collected in two periods: dry and rainy season of 2013. The lipid biomarker-based assessment was performed by applying ultrasonic extraction and gas chromatography coupled with mass spectrometry. Aliphatic hydrocarbon concentrations ranged from 0.50 μg g-1 to 0.94 μg g-1, whereas polycyclic aromatic hydrocarbons and fatty acids ranged from 17.96 ng g-1 to 40.61 ng g-1 and 1.63 μg g-1 to 1.54 μg g-1, respectively. The n-alkanes distribution showed the predominance of hydrocarbons originated from terrestrial plants in the two seasons, whereas PAH might be introduced in the estuary by fossil fuel combustions and wildfire. Fatty acid distributions indicated that the organic matter, which is mainly originated from terrestrial sources, has been constantly recycled by microorganisms. Furthermore, incorrect discharge of wastewater was observed in some areas near Brejo Grande and Povoado Cabeço. Although polycyclic aromatic hydrocarbons concentrations found in this study were lower in comparison with other highly impacted estuarine systems worldwide, benzo[a]pyrene, a compound known by its carcinogenic potential, was the most abundant PAH in the two periods, which might represent a chronic risk to the biota in the São Francisco River Estuary.